UWB device for breast microwave imaging: phantom and clinical validations. (November 2019) - Vispa, Alessandro; Sani, Lorenzo; Paoli, Martina; Bigotti, Alessandra; Raspa, Giovanni; Ghavami, Navid; Caschera, Stefano; Ghavami, Mohammad; Duranti, Michele; Tiberi, Gianluigi
Highlights: Huygens principle microwave imaging gives homogeneity maps of dielectric properties. Microwave apparatus does not require any breast compression or any matching liquid. MAX/AVG is used to measure the non-homogenous behavior of images. Detection of inclusions in phantoms is achieved. MAX/AVG is statistically robust to discriminate between healthy/non-healthy breasts. Abstract: Microwave imaging has received increasing attention in the last decades, motivated by its application in diagnostic imaging. Such effort has been encouraged by the fact that, at microwave frequencies, it is possible to distinguish between tissues with different dielectric properties. In such framework, a novel microwave device is presented here. The apparatus, consisting of two antennas operating in air, is completely safe and non-invasive since it does not emit any ionizing radiation and it can be used for breast lesion detection without requiring any breast crushing. We use Huygens Principle to provide a novel understanding into microwave imaging; specifically, the algorithm based on this principle provides images which represent homogeneity maps of the dielectric properties (dielectric constant and/or conductivity). The experimental results on phantoms having inclusions with different dielectric constants are presented here. In addition, the capability of the device to detect breast lesions has been verified through clinical examinations on 51 breasts. We introduce a metric to measure the non-homogenous behaviour of the image, establishing a modality to detect the presence of inclusions inside phantoms and, similarly, the presence of a lesion inside a breast.